Singapore : Staff Report for the 2004 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This 2004 Article IV Consultation highlights that in recent years, Singapore's economy has been hit hard by a series of external shocks. These shocks-the Asian crisis, the bursting of the technology bubble, and the SARS outbreak in 2003-disrupted an economic expansion largely uninterrupted since the 1970s. The shocks have come at a time when Singapore is also facing increasing competition from regional low-cost economies. Looking ahead, economic activity is expected to moderate to more sustainable levels in the near term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet